2021
DOI: 10.1007/s10008-021-05061-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited molybdenum-doped Co3O4 nanosheet arrays for high-performance and stable hybrid supercapacitors

Abstract: Long-cycle stability and high-energy density are big challenges for developing high-performance hybrid supercapacitor (HSC) electrode materials. In this work, molybdenum-doped Co 3 O 4 nanosheets arrays on nickel foam (noted as Mo x Co 1.5−x O/ NF) are successfully prepared via facile one-step electrodeposition followed by annealing for hybrid supercapacitors. The experimental and calculated results indicate that the band gap modification and conductivity enhancement of Mo x Co 1.5−x O lead to excellent capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Mo-doping of Co 3 O 4 by various methods (sol-gel, electrodeposition, and hydrothermal) has been investigated as a means to synthesize potential electrode materials [ 10 , 11 ]. Shen et al developed Mo-Co 3 O 4 nanosheets as a battery-type electrode for supercapacitor applications and reported a specific capacity of 128.2 mAh/g at 1 A/g with 95% of capacity retention after long-term cyclings [ 12 ]. The experimental results were substantiated by theoretical calculations; it was shown that Mo-doping of Co 3 O 4 modifies the bandgap and increases the electronic conductivity of the parent material, which enhances charge storage capability.…”
Section: Introductionmentioning
confidence: 99%
“…Mo-doping of Co 3 O 4 by various methods (sol-gel, electrodeposition, and hydrothermal) has been investigated as a means to synthesize potential electrode materials [ 10 , 11 ]. Shen et al developed Mo-Co 3 O 4 nanosheets as a battery-type electrode for supercapacitor applications and reported a specific capacity of 128.2 mAh/g at 1 A/g with 95% of capacity retention after long-term cyclings [ 12 ]. The experimental results were substantiated by theoretical calculations; it was shown that Mo-doping of Co 3 O 4 modifies the bandgap and increases the electronic conductivity of the parent material, which enhances charge storage capability.…”
Section: Introductionmentioning
confidence: 99%
“…By adjusting the voltage, pulse frequency, space between the components, deposition duration, and the use of nonconductive masks, porosity can be controlled through this technique. Electrodeposition has drawn attention in different applications (e.g., capacitors, [132][133][134] batteries, 135,136 DSSCs, [137][138][139] electrochemistry 133,[140][141][142] ). Fig.…”
Section: Rsc Applied Interfaces Reviewmentioning
confidence: 99%
“…Electrodeposition has drawn attention in different applications ( e.g. , capacitors, 132–134 batteries, 135,136 DSSCs, 137–139 electrochemistry 133,140–142 ). Fig.…”
Section: Synthesis Of Nanoporous Oxidesmentioning
confidence: 99%
“…At a current density of 1 A g −1 , a high specific capacity of 923 F g −1 is displayed by the optimized Mo 0.25 Co 1.25 /NF electrode. A white LED is also lit for 3.5 min by two series of HSCs 25 …”
Section: Synthesis Strategiesmentioning
confidence: 99%
“…A white LED is also lit for 3.5 min by two series of HSCs. 25 The electrodeposition approach is used to create the 3D ternary composite PPy/rGO/ZrO 2 by electrochemically polymerizing the pyrrole monomer, electrochemically reducing the GO, and creating ZrO 2 nanoparticles. Pyrrole, zirconyl chloride octahydrate, sodium para-toluene sulfonate, and GO are combined in an aqueous dispersion in deionized water.…”
Section: Electrodeposition Strategymentioning
confidence: 99%